Prime-boost vaccination with chimeric antigens adjuvanted in Montanide™ ISA50 V2 confers protection against experimental Lepeophtheirus salmonis infestation in Atlantic salmon (Salmo salar L.) - Rodríguez, Alianet; Gadan, Koestan; Pérez, Lincidio; Evensen, Øystein; Estrada, Mario Pablo; Carpio, Yamila (Frontiers in Immunology, 2025)
IntroductionSea lice are crustacean ectoparasites affecting Atlantic salmon production worldwide and impediments to industry growth. Chemical treatment has been the method of choice to control infestation with increasing resistance. Vaccination is an environmentally friendly alternative for sea lice control; however, obtaining high levels of lice reduction through active immunization has proven difficult. This study aimed to explore the efficacy of two sea lice vaccine prototypes under laboratory-controlled conditions.MethodsTherein, fish were vaccinated with two chimeric antigens, TT-P0 or P0-my32, using oil-adjuvanted vaccine formulations and a prime-boost vaccination protocol. Fish were experimentally challenged with copepodids at 2, 5, and 11 months post-prime vaccination.Results and discussionTT-P0 vaccinated fish had a significantly lower lice number at all three challenges, 88, 90, and 20%, respectively, compared to controls. The P0-my32 vaccine gave high protection at early time points post-vaccination, with 91 and 75.4% reduction at 3 and 6 months, respectively, fading off at 12 months (4.2% reduction vs. control). The TT-P0 group had a significantly lower lice number than controls at the 11-month challenge. A higher degree of protection coincided with higher circulating antibody levels against homologous antigens. This proof of concept study encourage the use of vaccination as a tool to reduce the lice burden in salmon, and preclinical and clinical testing at a large scale is needed to document the level of protection attained under field conditions.